Graphene enriched with pyrrolic coordination of the doped nitrogen as an efficient metal-free electrocatalyst for oxygen reduction - Unni, SreeKuttan M.; Devulapally, Saikrishna; Karjule, Neeta; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
We report an efficient template-free synthetic route for the preparation of mesoporous nitrogen-doped graphene (NGE) containing a high weight percentage of pyrrolic nitrogen, good specific surface area and comparable electrochemical oxygen reduction activity as that of the state-of-the-art 40 wt% Pt/C catalyst. The desired coordination of nitrogen in the carbon framework of graphene has been conceived by a mutually assisted redox reaction between graphene oxide (GO) and pyrrole, followed by thermal treatment at elevated temperatures. NGE exhibits a high surface area of 528 m(2) g(-1) and a pore diameter of similar to 3 to 7 nm. The heat treatment temperature plays a pivotal role in establishing the desired pyrrolic coordination of nitrogen in graphene for the electrochemical oxygen reduction reaction. The NGE sample obtained after heat treatment at 1000 degrees C (NGE-1000) has 53% pyrrolic nitrogen content compared to the similar samples prepared by treating at low temperatures. Most importantly, NGE-1000 has displayed a significantly low overpotential for oxygen reduction with the onset potential very closely matching that of the commercial 40 wt% Pt/C. It is noteworthy that the reaction involves the desired 4 electron transfer as observed in the case of the Pt based electrocatalysts, leading to a significantly high kinetic current density of 6 mA cm(-2) at -0.2 V. Moreover, the fuel tolerance and durability under the electrochemical environment of the NGE catalyst is found to be superior to the Pt/C catalyst.

Heterotriangulene-based unsymmetrical squaraine dyes: synergistic effects of donor moieties and out-of-plane branched alkyl chains on dye cell performance - Karjule, Neeta; Munavvar, Fairoos M. K.; Nithyanandhan, Jayaraj (Journal of Materials Chemistry A, 2016)
Unsymmetrical squaraine sensitizers with two different donor moieties, triphenylamine (NSQR) and heterotriangulene (NSQ1–3), for dye-sensitized solar cells (DSSCs) have been designed and synthesized. These dyes utilize the indolium moiety to control charge recombination dynamics at the TiO2-dye-electrolyte interface by connecting linear and branched alkyl functionalities. In the present study, an efficient heterotriangulene (HT) donor and a branched alkyl group at sp3-C atoms were strategically incorporated to increase the power conversion efficiency (PCE) of zwitterionic dyes by improving photo-current density (Jsc) and open-circuit potential (Voc) of the cell. Among these four dyes, NSQ3 exhibited the highest efficiency of 6.73% with a Jsc of 18.74 mA cm−2, Voc of 0.53 V, and fill factor (ff) of 68.3%, without any co-adsorbent under an irradiance of 100 mW cm−2 (simulated AM 1.5G sunlight). In the presence of 3α,7α-dihydroxy-5β-cholanic acid (CDCA), NSQ1, NSQ2 and NSQ3 showed an efficiency of 7.07%, 7.38% and 7.17%, respectively. Despite the low Voc, far red light harvesting efficiency, reduced dye aggregation, long lifetime (τ) of injected electrons and high quantum efficiency of NSQ1–3 played constructive roles in achieving high PCE efficiency. Deceleration of charge recombination for NSQ dye cells was further studied by electrochemical impedance spectroscopy (EIS) and open-circuit photo-voltage decay (OCVD) measurements.

Molecular control of the band edge movement and the recombination process in donor-acceptor hemicyanine-sensitized solar cells - Karjule, Neeta; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2017)
The presence of downward shift in the band edge and the recombination reactions in the hemicyanine-sensitized solar cell reduces the open-circuit potential (V-oc) and the short-circuit current density (J(sc), which in turn decreases the dye cell performance. Choosing either an electrolyte possessing minimum overpotentials or a systematic dye design which can efficiently suppress the diffusion of charged species toward the TiO2 can improve the overall power conversion efficiency (PCE). Here, a series of donor acceptor (D-A) hemicyanine dyes were synthesized utilizing a planar heterotriangulene (HT) or triphenylamine (TPA) donor and alkyl-functionalized indolium carboxylic acid acceptor unit. By introducing strong HT donor instead of TPA, the photophysical, and electrochemical properties of D-A dyes are significantly modulated. The strong donor nature of HT and effective passivation of surface by hydrophobic alkyl chains close to the anchoring group for NC3 dye exhibits an average PCE of 4.34% with a V-oc of 0.416 V, J(sc) of 20.04 mA cm(-2), and fill factor (ff) of 52.03% under simulated AM 1.5G illumination (100 mW cm-2) without 3 alpha,7 alpha-adihydroxy-5 beta-cholic acid coadsorbent (CDCA). The intrinsic dipole of the hemicyanine dye and the presence of Li+ ions in iodide/triiodide redox couple without tert-butylpyridine (TBP) additive induces a downward shift in conduction band edge (E-CB) of TiO2. By rational molecular design, the extend of shift in E-CB is controlled and enhanced the V-oc. Electrochemical impedance spectroscopy (EIS) studies revealed the high charge transfer resistance (R-ct) and long lifetime (tau) of injected electrons in HT-based dyes than that of TPA derivatives, which provide insight into the passivation of Li+ and I- ions by current D-A dye design possessing alkyl functionalities to increase both the J(sc) and V-oc.

Fused fluorenylindolenine-donor-based unsymmetrical squaraine dyes for dye-sensitized solar cells - Bisht, Rajesh; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Karjule, Neeta; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
A series of four unsymmetrical squaraine dyes, XSQ1-4, were synthesized using a fused fluorenylindolenine-based donor unit for dye-sensitized solar cells (DSSCs). The fused structure of fluorenylindolenine helped in moving the absorption toward the near-infrared (NIR) region, and the two sp(3)-C centers available on this donor were utilized to incorporate out-of-plane alkyl chains in opposite directions to control the dye-dye interactions on the TiO2 surface. High extinction coefficient (epsilon >= 10(5) M-1 cm(-1)) for absorbing NIR photons and suitable highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with respect to the conduction band of TiO2 and electrolyte for charge injection and dye regeneration processes, respectively, make these dyes potential sensitizers for DSSCs. Introduction of branched alkyl groups in the pi-framework helped in controlling dye aggregation to reduce exciton quenching and assisted in TiO2 surface passivation to avoid the charge recombination process. Furthermore, having a naphthyl group on the indole part of the anchoring group containing segment helped to red-shift the absorption spectrum of dyes 15 nm toward the NIR region (XSQ3-4). Among all of the dyes under investigation, XSQ2 gave the best photovoltaic performance, having a short-circuit current density (J(SC)) of 13.99 mA cm(-2), open -circuit voltage (V-OC) of 0.66 V, and a fill factor (ff) of 0.71, with a device performance (eta) of 6.57%. Electrochemical impedance spectroscopy revealed higher electron lifetime on TiO2 for XSQ2, which helps to avoid the charge recombination process.
Keywords: Dye-sensitized solar cells; fluorenylindolenine; H- and J-type aggregation; NIR absorption; out-of-plane alkyl groups; squaraine dyes

Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.